Choroidal vascular changes in internal carotid artery stenosis: a retrospective cohort study in Chinese population - Li, Shuang (BMC Ophthalmol, 2019)
BACKGROUND: To evaluate choroidal vascularity index (CVI) in eyes with internal carotid artery (ICA) stenosis using binarization tool in enhanced depth images scanned by spectral domain optical coherence tomography. METHODS: A retrospective cohort study was conducted in 142 patients with ICA stenosis, and 20 normal control subjects matched with the age, sex, etc. According to the diagnostic criteria, the participants are divided into a normal control group (20 cases), a mild stenosis group (64 cases), a moderate stenosis group (61 cases), and a severe stenosis group (17 cases). Enhanced depth imaging optical coherence tomography (EDIOCT) was performed to scan macular fovea, which was separated into a luminal area and a stromal area using image binarization. The choroidal vascularity index (CVI) is luminal area divided by total choroidal area. RESULTS: There was no statistical difference in age or sex among groups. Subfoveal choroidal thickness (SFCT) in the severe stenosis group was significantly lower than that in the normal group (P < 0.05). Moreover, the CVI in moderate stenosis group and severe stenosis group were significantly lower compared with the normal control group (P < 0.001). When CVI = 65.16% was set as the cut-off value, all 162 subjects could be divided into two groups, CVI ≤ 65.16 (n = 83) and CVI > 65.16% (n = 79). The proportions of mild stenosis, moderate stenosis, and severe stenosis in CVI ≤ 65 .16 group and CVI > 65.16% group were statistically significant (P < 0.001). CONCLUSION: CVI may be a useful indicator for early diagnosis and monitoring of choroidal vascular changes in ICA stenosis.